Distinct epitope structures of defensin‐like proteins linked to proline‐rich regions give rise to differences in their allergenic activity. Issue 2 (27th September 2017) - Pablos, I.; Eichhorn, S.; Machado, Y.; Briza, P.; Neunkirchner, A.; Jahn‐Schmid, B.; Wildner, S.; Soh, W. T.; Ebner, C.; Park, J.‐W.; Pickl, W. F.; Arora, N.; et al.
Abstract: Background: Art v 1, Amb a 4, and Par h 1 are allergenic defensin‐polyproline–linked proteins present in mugwort, ragweed, and feverfew pollen, respectively. We aimed to investigate the physicochemical and immunological features underlying the different allergenic capacities of those allergens. Methods: Recombinant defensin‐polyproline–linked proteins were expressed in E. coli and physicochemically characterized in detail regarding identity, secondary structure, and aggregation status. Allergenic activity was assessed by mediator releases assay, serum IgE reactivity, and IgE inhibition ELISA using sera of patients from Austria, Canada, and Korea. Endolysosomal protein degradation and T‐cell cross‐reactivity were studied in vitro. Results: Despite variations in the proline‐rich region, similar secondary structure elements were observed in the defensin‐like domains. Seventy‐four percent and 52% of the Austrian and Canadian patients reacted to all three allergens, while Korean patients were almost exclusively sensitized to Art v 1. This was reflected by IgE inhibition assays demonstrating high cross‐reactivity for Austrian, medium for Canadian, and low for Korean sera. In a subgroup of patients, IgE reactivity toward structurally altered Amb a 4 and Par h 1 was not changed suggesting involvement of linear epitopes. Immunologically relevant endolysosomal stability of the defensin‐like domain was limited to Art v 1 and no T‐cell cross‐reactivity with Art v 125‐36 was observed. Conclusions: Despite structural similarity, different IgE‐binding profiles and proteolytic processing impacted the allergenic capacity of defensin‐polyproline–linked molecules. Based on the fact that Amb a 4 demonstrated distinct IgE‐binding epitopes, we suggest inclusion in molecule‐based allergy diagnosis.